Association of Serum Osmolarity With Contrast-Induced Nephropathy in Patients With ST-Segment Elevation Myocardial Infarction. (August 2019) - Yildiz, Ibrahim; Yildiz, Pinar Ozmen; Rencuzogullari, Ibrahim; Karabag, Yavuz; Cagdas, Metin; Burak, Cengiz; Gurevin, Mehmet Sait
Contrast-induced nephropathy (CIN) is a prevalent and serious complication after primary percutaneous coronary intervention (pPCI). Although the association between serum osmolarity and chronic kidney disease is well established, its relation to CIN in patients with ST-segment elevation myocardial infarction (STEMI) undergoing pPCI needs to be elucidated. We evaluated the predictive value of serum osmolarity for CIN development in patients with STEMI (n = 768) undergoing pPCI. Serum osmolarity on admission was calculated. The study population was divided into 2 groups according to CIN development, and both groups were compared according to clinical, laboratory, and demographic features, including the serum osmolarity. Serum osmolarity was significantly higher in patients with CIN than in those without CIN (278 [8] vs 284 [9]; P = .024). Serum osmolarity (odds ratio: 1.052; 95% confidence interval: 1.018-1.086; P = .002), hemoglobin, contrast media volume, creatinine on admission, basal SYNergy between PCI with TAXus and cardiac surgery II score, and left ventricular ejection fraction were found to be independent predictors of CIN. Serum osmolarity (given the simple calculation of this parameter on admission) can be useful to define patients with STEMI undergoing pPCI who are more likely to develop CIN.